2011
DOI: 10.1016/j.virol.2011.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Human polyomavirus JC small regulatory agnoprotein forms highly stable dimers and oligomers: Implications for their roles in agnoprotein function

Abstract: JC virus (JCV) encodes a small basic phosphoprotein from the late coding region called agnoprotein, which has been shown to play important regulatory roles in the viral replication cycle. In this study, we report that agnoprotein forms highly stable dimers and higher order oligomer complexes. This was confirmed by immunoblotting and mass spectrometry studies. These complexes are extremely resistant to strong denaturing agents, including urea and SDS. Central portion of the protein, amino acids spanning from 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
76
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(85 citation statements)
references
References 72 publications
9
76
0
Order By: Relevance
“…To support this notion in functional assays, we demonstrated that agnoprotein enhances the DNA binding activity of LT-Ag to the viral origin (Ori) without itself directly interacting with DNA (4). We also demonstrated that agnoproteins of BKV, SV40, and JCV form highly stable, SDS-resistant homodimers and oligomers (7,18). In particular, the Leu/Ile/Phe-rich region of the protein plays a direct role in forming such structures and is required for the stable expression of the protein (1).…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…To support this notion in functional assays, we demonstrated that agnoprotein enhances the DNA binding activity of LT-Ag to the viral origin (Ori) without itself directly interacting with DNA (4). We also demonstrated that agnoproteins of BKV, SV40, and JCV form highly stable, SDS-resistant homodimers and oligomers (7,18). In particular, the Leu/Ile/Phe-rich region of the protein plays a direct role in forming such structures and is required for the stable expression of the protein (1).…”
mentioning
confidence: 84%
“…As we previously demonstrated, the stable dimer and oligomer formation by agnoprotein can be monitored by employing SDS-PAGE under reducing conditions, followed by Coomassie blue staining in vitro (1,7). As shown in Fig.…”
Section: Agnoprotein Is Predicted To Contain a Hydrophobic ␣-Helixmentioning
confidence: 98%
See 2 more Smart Citations
“…Agnoprotein is a 71 aa multi-functional protein with numerous reported protein-protein interactions (Darbinyan et al, 2004;Endo et al, 2003;Johannessen et al, 2008;Safak et al, 2002;Suzuki et al, 2005). It also retains a central hydrophobic TMD which, along with an N-terminal region, is required for ER/plasma membrane localization and membrane integration (Suzuki et al, 2010), and forms stable oligomers within infected cells (Coric et al, 2014;Saribas et al, 2011Saribas et al, , 2013Suzuki et al, 2010). Agnoprotein expression both increases plasma membrane permeability and elevates cytosolic calcium, resulting in enhanced virion release (Suzuki et al, 2010).…”
Section: Dna Virus Viroporinsmentioning
confidence: 99%